Analisis Pengaruh Jangka Pendek dan Jangka Panjang Nilai Tukar dan Tingkat Imbalan SBIS Terhadap Inflasi di Indonesia Periode Januari 2009-Desember 2015 - Tania Megasari; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The purpose of this research is to examine the effect of the exchange rate, and the return rate of Bank Indonesia Sharia Certificate (SBIS) on inflation in Indonesia during the period January 2009 to December 2015. The approach used in this research is quantitative research using Error Correction Model (ECM) by Eviews program 8. The data used are secondary data from the official website of Bank Indonesia. The results showed that the Exchange rate and the rate of SBIS have a significant and positive correlation against inflation in the short term and long term during the period January 2009 to December 2015.